Sensitivity to extracellular potassium underlies type-intrinsic differences in retinal ganglion cell excitability - Boal, Andrew M.; McGrady, Nolan R.; Risner, Michael L.; Calkins, David J. (Frontiers in Cellular Neuroscience, 2022)
Neuronal type-specific physiologic heterogeneity can be driven by both extrinsic and intrinsic mechanisms. In retinal ganglion cells (RGCs), which carry visual information from the retina to central targets, evidence suggests intrinsic properties shaping action potential (AP) generation significantly impact the responses of RGCs to visual stimuli. Here, we explored how differences in intrinsic excitability further distinguish two RCG types with distinct presynaptic circuits, alpha ON-Sustained (αON-S) cells and alpha OFF-Sustained (αOFF-S) cells. We found that αOFF-S RGCs are more excitable to modest depolarizing currents than αON-S RGCs but excitability plateaued earlier as depolarization increased (i.e., depolarization block). In addition to differences in depolarization block sensitivity, the two cell types also produced distinct AP shapes with increasing stimulation. αOFF-S AP width and variability increased with depolarization magnitude, which correlated with the onset of depolarization block, while αON-S AP width and variability remained stable. We then tested if differences in depolarization block observed in αON-S and αOFF-S RGCs were due to sensitivity to extracellular potassium. We found αOFF-S RGCs more sensitive to increased extracellular potassium concentration, which shifted αON-S RGC excitability to that of αOFF-S cells under baseline potassium conditions. Finally, we investigated the influence of the axon initial segment (AIS) dimensions on RGC spiking. We found that the relationship between AIS length and evoked spike rate varied not only by cell type, but also by the strength of stimulation, suggesting AIS structure alone cannot fully explain the observed differences RGC excitability. Thus, sensitivity to extracellular potassium contributes to differences in intrinsic excitability, a key factor that shapes how RGCs encode visual information.